Chemical vapour deposition : precursors, processes and applications - Jones, Anthony C.; Hitchman, Michael L. (Royal Society of Chemistry, 2009)
Chemical Vapour Deposition (CVD) involves the deposition of thin solid films from chemical precursors in the vapour phase, and encompasses a variety of deposition techniques, including a range of thermal processes, plasma enhanced CVD (PECVD), photon- initiated CVD, and atomic layer deposition (ALD). The development of CVD technology owes a great deal to collaboration between different scientific disciplines such as chemistry, physics, materials science, engineering and microelectronics, and the publication of this book will promote and stimulate continued dialogue between scientists from thes.
Keywords: Chemical vapor deposition.; elektronické knihy; electronic books